Molecular characterization of five predicted DNA-binding proteins in Ehrlichia chaffeensis - Alizadeh, Kimia (Kansas State University, 2023)
Tick-borne diseases are considered as a major concern threatening the health of people and many other vertebrate hosts. Ticks can transmit a variety of pathogens including viruses, bacteria and parasites from one host to another while acquiring their blood meal. Ehrlichia chaffeensis is an important tick-borne pathogen responsible for the disease, monocytic ehrlichiosis. This Gram-negative intracellular pathogen is able to survive in a variety of host species including ticks and vertebrate hosts. Understanding how this pathogen is able to maintain its infectivity in multiple hosts is critical for development of methods of control. We have studied how E. chaffeensis overcomes the clearance by both tick and canine hosts. This research was conducted through multiple molecular manipulation experiments to further our understanding of bacterial gene regulation. We determined the transcription variations for five predicted DNA-binding proteins in E. chaffeensis: MerR, EcxR, CtrA, Hu and Tr1, while transitioning from reticulate cell (RC) form to dense core cell (DC) form and vice versa, and variations resulting from type of host cell to investigate how such differences impact gene regulation. We defined the expression of all five predicted transcription regulators at the RNA level and demonstrated unique RNA expression patterns in vertebrate and tick host cells and in the RC and DC forms. Additionally, we identified the protein expression for all five predicted transcription regulators for DC and RC forms of E. chaffeensis, purified from both host cell backgrounds using protein-specific antibody. This research will help advancing our knowledge on gene regulation in bacteria, providing means for more efficient prevention and control.
Keywords: Ehrlichia chaffeensis; Tick-borne disease; DNA-binding protein; Transcription regulation